Աղբակի գավառակում հայերի դեմ իրականացված ցեղասպանական գործողությունները 1914-1915 թթ. - Մաթոսյան, Սաթենիկ Ա. (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
In the Aghbak sub-district, there were 36 Armenian villages, six of which are used as examples to present the brutal massacres, violence, and subsequent forced deportations of Armenians in 1914–1915, based on predominantly archival sources. These examples not only highlight the systematic nature of the atrocities but also reveal the active involvement of both local Kurdish tribes and Ottoman authorities in implementing these acts. The Aghbak sub-district, strategically located near trade routes and the Persian border, was targeted due to its economic significance and geographic vulnerability during the war. This was one of the first attempts at genocidal actions carried out by the Ottoman Empire during World War I. В районе Ахбак было 36 армянских деревень, на примере шести из которых представлены жестокие массовые убийства, насилие и последовавшие за ними насильственные депортации армян в 1914–1915 гг., основанные на различных, преимущественно архивных, источниках. Эти примеры не только подчеркивают систематический характер преступлений, но и раскрывают активное участие как местных курдских племен, так и османских властей в их осуществлении. Ахбак, находившийся вблизи торговых путей и персидской границы, стал мишенью из-за своей экономической значимости и географической уязвимости во время войны. Это была одна из первых попыток геноцидиальных действий, осуществленных Османской империей во время Первой мировой войны.
Keywords: Հայոց ցեղասպանություն